(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Rare earth orthovanadates are widely used in optical electronic devices due to their interesting optic, magnetic and electrophysical properties. It is known that properties of composite oxides can essentially depend on method of synthesis. Choosing one or other method of preparation enables one to influence the structural and morphological characteristics (degree of crystallinity, porosity, grain size) as well as optical and electrical properties. Therefore, aim of our work is to investigate dependencies of spectral properties on method of synthesis. The samples La1-xEuxVO4 obtained by the solid-state reaction and co-precipitation method. The La1-xEuxVO4 (0 £x £0.3) compounds were identified using x-ray diffraction (XRD). It was found that the samples obtained by the solid state method are single phase, as well as those obtained using co-precipitation of components. The crystal structure of pure lanthanum ortovanadates LaVO4 is monoclinic, space group P21/n with a = 0.7045(1) nm, b = 0.7281(1) nm, c = 0.6725(1) nm, β = 104.854(1) for solid state synthesis method and a = 0.7043(3) nm, b = 0.7280(1) nm, c = 0.6722(2) nm, b = 104.855(1) for co-precipitation synthesis method. In two series of the La1‑xEuxVO4 solid solutions with increasing component concentration of europium at substitution lanthanum on europium the changing from monoclinic phase to tetragonal (space group I41/amd) is observed. We have studied the morphology (that may consist of one or several crystallites) and size of particles using scanning electron microscopy (SEM). Luminescence of the Eu3+ ions can be excited in the La1‑xEuxVO4 solid solutions directly by inner transitions in the impurity ions. Energy transfer from the crystal matrix to the Eu3+ ions takes place. Efficiency of energy transfer from matrix to the Eu3+ ions depends on method of synthesis of and on concentration of the Eu3+ ions. We consider that features of crystal microstructures and neighbor surrounding of the Eu3+ ions influence on efficiency of energy transfer to centers of the Eu3+ emission.